Differences in psychological and somatic symptom cluster score profiles between subjects with Idiopathic environmental intolerance, major depression and schizophrenia. (March 2017) - Weiss, Elisabeth M.; Singewald, Evelin; Baldus, Claudia; Hofer, Ellen; Marksteiner, Josef; Nasrouei, Sarah; Ruepp, Beatrix; Kapfhammer, Hans-Peter; Fitz, Werner; Mai, Christoph; Bauer, Anke; Papousek, Ilona; et al.
Abstract: Idiopathic Environmental Intolerance (IEI) has been associated with psychogenic factors and an increased number of comorbid psychiatric disorders such as depression and anxiety disorder. The purpose of the current study was to examine a possible overlap of psychological and somatic symptoms between subjects with IEI and patients with major depression and schizophrenia as well as to specify characteristic differences. The different symptom clusters included symptoms of chemical intolerance, neurotoxicity and psychological distress as well as measurements of mental health such as anxiety, depression, somatoform symptoms, and schizophrenia-specific disturbances in cognitive domains. IEI patients reported higher overall levels in physical symptoms such as chemical intolerance, neurotoxicity and somatic symptoms not attributable to an organic cause. Schizophrenia patients showed higher overall levels in self-experienced disturbances in several schizophrenia-specific cognitive domains, whereas general psychological distress, anxiety and depression were rated highest by patients with major depression. Importantly, the groups markedly differed in the shapes of profiles of various symptom clusters. Our results provide evidence that IEI patients can be distinguished on the phenomenological level from patients with major depression or schizophrenia, and that distinct domains of psychological and somatic symptoms are particularly problematic in specific diagnostic groups. Highlights: IEI is highly prevalent and associated with different comorbid psychiatric disorders. IEI patients can be distinguished on the phenomenological level from Axis I disorders. Overall symptom cluster level and symptom profile shape are different between groups. We could show differences in the shapes of profiles of various symptom clusters. Distinct domains of psychological/somatic symptoms are problematic in these groups.